2020
DOI: 10.1111/cdoe.12528
|View full text |Cite
|
Sign up to set email alerts
|

The oral health of refugees: Issues and challenges arising from a case series analysis

Abstract: Community Dent Oral Epidemiol. 2020;48:195-200. | 195 wileyonlinelibrary.com/journal/cdoe | INTRODUC TI ONRefugees constitute a heterogeneous population. Coming from different backgrounds, they experience, in their own and hosting countries, a wide range of practices that may affect their health. 1 It is generally acknowledged that refugees have greater health needs and concerns than most immigrants, partly arising from the refugee experience and resettlement process. 1 In situations of political and social un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(49 citation statements)
references
References 19 publications
2
47
0
Order By: Relevance
“…However, no studies have evaluated refugee satisfaction regarding provided services. Limited availability/access to basic health services, including dental care, nutrition, immunization, preventive care and chronic disease management, is a major challenge to refugees [ 7 , 15 ]. It is important to provide data to guide service provision and clinical management according to patient-based approaches.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, no studies have evaluated refugee satisfaction regarding provided services. Limited availability/access to basic health services, including dental care, nutrition, immunization, preventive care and chronic disease management, is a major challenge to refugees [ 7 , 15 ]. It is important to provide data to guide service provision and clinical management according to patient-based approaches.…”
Section: Discussionmentioning
confidence: 99%
“…The present study found that most elements under human and physical health resources range from acceptable to very satisfied, except for ‘ease of access to general/oral health facilities’ and ‘availability of all dental services’. It has been reported previously that the attitude of non-attendance or delays in obtaining dental/medical treatment are strongly associated with accessibility, income, availability of healthcare facilities and perception of the need for routine dental care; all of which are major concerns for the refugee population [ 7 , 26 ]. Furthermore, extended waiting times for emergency and routine dental treatment are associated with higher rates of amplified deterioration of teeth [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations